Time to establish pillars in point‐of‐care ultrasound. Issue 1 (19th February 2019) - Cormack, Carolynne J.; Wald, Anthony M.; Coombs, Peter R.; Kallos, Leah; Blecher, Gabriel E.
Abstract: Point of care ultrasound (PoCUS) has evolved rapidly and is used by many medical specialties. We propose five essential pillars of PoCUS that are necessary framework for hospital‐based PoCUS training and credentialing programs. The pillars are: governance, infrastructure, administration, education and quality. It is time to establish these pillars to ensure the best practice in PoCUS use.